A comparative volatilomic characterization of Florence fennel from different locations: antiviral prospects. Issue 4 (22nd January 2021) - Ibrahim, Nehal; Moussa, Ashaimaa Y.
Abstract : Volatilomic profiling of Florence fennel with anti-HAV protease and anti-HCV polymerase activities and best fitting phytomarkers. Abstract : The genus Foeniculum is known for its wide ethnobotanical use in the Mediterranean region. Herein, we explored the compositional differences of volatile oils and headspace aroma of Florence fennel ( Foeniculum vulgare var. azoricum (Mill.) Thell.) based on its different organs and various geographical origins via gas chromatography coupled with mass spectrometry (GC-MS). Sixty-seven volatile components were detected with phenylpropenes and monoterpenes, including trans -anethole, limonene, α-pinene, trans -β-ocimene, fenchyl acetate, and fenchone, as major constituents. Phenylpropenes were dominant in fennel hydro-distilled oils, whereas monoterpenes were dominant in most of the headspace aroma. The infraspecific variability was assessed using the unsupervised multivariate data analysis tools PCA and HCA, resulting in segregate clustering of accessions from different organs and locations with trans -anethole, limonene, trans -β-ocimene, fenchone, myristicin, and apiole as major phytomarkers contributing to this segregation. The antiviral activities of samples against hepatitis A and C viruses were investigated using the plaque reduction assay, HAV 3C proteinase and HCV NS5B polymerase inhibitory assays with a percentage inhibition between 66% and 85% and IC50 values from 1.8 to 26.7 μg mL −1 . In silico molecular docking scores in latter enzyme binding pockets revealed key allosteric interactions with trans -β-ocimene and β-fenchyl acetate showing the best Gibb's free energy. Florence fennel exhibited interesting new perspectives for medicinal and industrial applications.